2017
DOI: 10.1016/s2095-3119(16)61462-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid gene expression change in a novel synthesized allopolyploid population of cultivated peanut×Arachis doigoi cross by cDNA-SCoT and HFO-TAG technique

Abstract: Allopolyploidy has played an important role in plant evolution and heterosis. Recent studies indicate that the process of wide hybridization and (or) polyploidization may induce rapid and extensive genetic and epigenetic changes in some plant species. To better understand the allopolyploidy evolutionism and the genetic mechanism of Arachis interspecific hybridization, this study was conducted to monitor the gene expression variation by cDNA-start codon-targeted (SCoT) polymorphism and cDNA-high-frequency oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The results showed that non-additive expression significantly differed among the eight synthetic allotetraploids of B. napus . This also proves that the newly synthesized allopolyploid is unstable, and the expression of genes in the selfed-offspring drastically changes [ 44 , 45 ]. Furthermore, the results of GO enrichment analysis were consistent with the hypothesis that “non-additive gene expression and multi-molecular mechanism promote heterosis”, which also indicates that non-additive expression genes play a key role in the field performance of offspring [ 26 ].…”
Section: Discussionmentioning
confidence: 80%
“…The results showed that non-additive expression significantly differed among the eight synthetic allotetraploids of B. napus . This also proves that the newly synthesized allopolyploid is unstable, and the expression of genes in the selfed-offspring drastically changes [ 44 , 45 ]. Furthermore, the results of GO enrichment analysis were consistent with the hypothesis that “non-additive gene expression and multi-molecular mechanism promote heterosis”, which also indicates that non-additive expression genes play a key role in the field performance of offspring [ 26 ].…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have shown that synthetic B. napus has abundant variation, such as in flowering time, flower size, plant fresh weight, leaf shape and size, the surface wax layer, and other traits [13,18]. However, there have been few studies on the mechanism of variation in traits in the field between different genetic combinations and different generations [14]. In our investigation of the field characteristics of synthetic B. napus, traits were separated in different combinations and generations.…”
Section: Discussionmentioning
confidence: 94%
“…Allopolyploid-induced variant DNA sequences are mainly concentrated in transposon sequences, random sequences, or repetitive sequences [31][32][33]. Through bioinformatics analysis, it was found that the microsatellite sequence density of the coding region in natural B. napus was higher than that of its diploid parent species, indicating that the SSRs in the gene coding region changed significantly during the polyploidization of B. napus [14,[34][35][36]. In our study, novel and missing SSR sequences were detected in the hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al [107] reported that transcript silencing, which could be reversible, resulted in a loss of gene or expression repressing, which was reported irreversible. As we found, one or more treatments resulted in losing transcripts (7 ScDNA out of 41 by 17%) (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%